Studi Pengelolaan Air Limbah Domestik Di PT Pertamina Patra Niaga Fuel Terminal Baturaja Provinsi Sumatera Selatan - Parasmita Anggraini; Syaiful Eddy; Andi Arif Setiawan; Wahyu Saputra; Jumingin Jumingin; Ita Emilia; Yunita Panca Putri (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
Industrial activities have the potential to produce solid, liquid, and gaseous waste from production processes and supporting activities. This condition also occurs at PT Pertamina Patra Niaga Fuel Terminal Baturaja, South Sumatra Province, as a fuel distribution company. The domestic wastewater produced has physical, chemical, and biological characteristics including pH, temperature, color, BOD, COD, TSS, oil and grease, and E-coli and coliform bacteria. Efforts made to minimize environmental impacts, the company implemented a study on domestic liquid waste management, especially greywater, through a treatment process and reuse as closed toilet rinse water. Wastewater treatment is carried out using a biofilter Wastewater Treatment Plant with a combination of anaerobic and aerobic processes. This study aims to assess the quality of wastewater in the inlet and outlet ponds of the WWTP. The research method uses primary and secondary data collection. The results of the analysis indicate that the quality of the processed wastewater has met the quality standards according to the Regulation of the Minister of Environment and Forestry Number P.68/MENLHK/Setjen/Kum.1/8/2016.